2020
DOI: 10.1007/s40544-020-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced micro/nano-tribological performance in partially crystallized 60NiTi film

Abstract: The microstructure, mechanical and micro/nano-tribological properties of the 60NiTi film annealed at different temperature were investigated. The results reveal that annealing as-deposited 60NiTi film at 300, 375, and 600 °C for 1 h leads to structural relaxation, partial crystallization and full crystallization, respectively. Compared with the structurally relaxed structure, the partially crystallized structure exhibits increased hardness but decreased elastic modulus. This is because that the elastic modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 67 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that the hardness enhancement of the WS 2 -metal composite coatings can be ascribed to solid solution strengthening effect. [31][32][33] The nanoindentation results revealed that the hardness of coating #1 with 47 at.% Nb doping was higher hardness than that of coating #2. After the tribotests of 300 °C and 400 °C, no significant change in the hardness of coating #2 was found.…”
Section: Coatings Nanoindentation and Friction Behavior Of The Worn S...mentioning
confidence: 99%
“…Studies have shown that the hardness enhancement of the WS 2 -metal composite coatings can be ascribed to solid solution strengthening effect. [31][32][33] The nanoindentation results revealed that the hardness of coating #1 with 47 at.% Nb doping was higher hardness than that of coating #2. After the tribotests of 300 °C and 400 °C, no significant change in the hardness of coating #2 was found.…”
Section: Coatings Nanoindentation and Friction Behavior Of The Worn S...mentioning
confidence: 99%